Creation of Ohmic contact on InGaAs/InAlAs quantum well detector for broad range photon detection - G, Tamiraa; A, Matias; H.M, Ralf; Biasiol, Giorgio (Scientific transaction of the National University of Mongolia. Physics, 2022)
Several applications utilizing either synchrotron or conventional light sources require fast and efficient pixelated detectors. In order to cover a wide range of experiments, this work investigates the possibility to use InGaAs/InAlAs quantum well devices as photon detectors for a broad range of energies. Owing to their direct, low-energy band gap and high electron mobility, such devices may be used also at room temperature as multi-wavelength sensors from visible light to hard X-rays. Three different metal configurations were tested to create Ohmic contacts on quantum well detectors. The triple layers of Au/Ge/Ni is a suitable metal to create good Ohmic contacts for the readout electrode. When the beam is hitting from the readout side, Al could be involved as contacting metal with annealing without requiring the etching.